Determination of Apoptosis Level of Hela Cells Treated with Disobinol Compound from Chisocheton Macrophyllus Plant - Hafiz, Ersanda; Albayyinah, Dyandra Hera; Melati, Rima; Herlina, Tati; Permadi, Nandang; Amalia, Riezki; Nurlelasari, Nurlelasari; Gaffar, Shabarni (Jurnal Riset Kimia, 2025)
Disobinol is a limonoid compound from the seeds of the Chisocheton macrophyllus plant that has been reported to have anticancer activity against cervical cancer cell lines. Cervical cancer is a type of cancer caused by infection with Human papillomavirus (HPV) types 16 and 18, leading to the transformation of normal cervical epithelial cells into cancerous cells. Previous studies show that Disobinol has a cytotoxic effect on HeLa cells with the IC50 value 52,92 μg/mL (24 hours’ incubation). This study aims to determine the level of apoptosis in HeLa cells treated with Disobinol and observe the DNA fragmentation in HeLa cells undergoing apoptosis. The HeLa cells were treated with Disobinol at concentrations of 26,5 μg/mL (1/2 IC50), 52,3 μg/mL (IC50), and 104,6 μg/mL (2x IC50) and incubated for 24 hours. The level of apoptosis was analyzed by using flow cytometry, and the DNA fragmentation pattern was analyzed by agarose gel electrophoresis. The results showed that Disobinol induces early apoptosis in HeLa cells, although the difference in the percentage of cell death is not very significant, which were 37.05%, 37.7%, and 41.60%, respectively. The DNA fragmentation pattern in HeLa cells treated with various concentrations of Disobinol was also observed on agarose gel. Therefore, Disobinol has the potential to be used as a chemotherapeutic drug or as a lead compound for the treatment of cervical cancer.